EFFECTS OF NOTE-TAKING STRATEGIES, ATTITUDINAL DIFFERENCES AND SOME PERSONALITY TRAITS ON STUDENTS' ACHIEVEMENT IN SOCIAL STUDIES (1995)
This study employed a 3x2x2 pretest-post test control group factorial design to investigate the effects of note-taking strategies, attitudinal differences and some personality traits on students' achievement in Social Studies. The subjects of the study were 96 first year Social Studies students of three Colleges of Education in Oyo and Osun States of Nigeria. Two experimental and one control groups were used. The first experimental group listened to taped lecture and wrote their own notes. The second listened to the taped lecture and followed lecturer's prepared notes while the control group listened only to audio-taped lectures on population studies. The Eysenck Personality Inventory (EPI) and the Students' Attitude to Social Studies Questionnaire (SASSQ) were utilised to categorize the subjects into extroverts and introverts, and to those with positive or negative attitude to social studies. Without any opportunity to review notes, subjects were made to take two post-tests - Social Studies Immediate Recall Test (SSIRT) and Social Studies Delayed Recall Test (SSDRT). Three dependent measures which were obtained for each subject were the pretest score, the immediate post-test score and the delayed post-test score. Data obtained were analyzed using Analysis of Covariance while Tukey Honestly Significant Difference tests were used for post hoc tests. The highlights of the results include the following: (1) There were statistically significant differences in the students' achievement on the basis of the different note-taking strategies adopted at both the immediate and delayed recall tests. Both the note-takers and note followers had significantly higher scores than the control group. (2) There were no statistically significant interactive effects of note-taking strategies and attitudinal differences on the students immediate recall test but there were statistically significant differences at the delayed recall test. (3) There were no statistically significant interactive effects of note-taking strategies and personality traits on the students' achievement at both the immediate and delayed recall test. (4) There were no statistically significant interactive effects of note-taking strategies, attitudinal difference and personality traits on students' achievement at both the immediate and delayed recall tests. The results are consistent with the idea that note-taking can be a generative activity that encourages students to build connections between lecture information and what they already know. This is one of the implications of the findings. Other implications were: that, rather than indulging in writing notes on the blackboard or in handouts for our students, they should be taught how to encode accurately lecture information during lecture; that sufficient practice in note-taking should be given to our students right from the lower levels of education; that whether a student is extrovertic or introvertic in his personality disposition, his achievement in social studies depends more on the type of note- taking strategy he adopts during class lectures; that positive attitude to learning enhances better remembering and recall. Suggestions were also made for further studies in the area of the research.